TỔNG HỢP VẬT LIỆU XÚC TÁC QUANG COMPOSITE AgI/BiVO4 NHẰM ỨNG DỤNG PHÂN HỦY CÁC CHẤT HỮU CƠ Ô NHIỄM - Mai Hùng Thanh Tùng; Trần Hải Yến; Trần Thị Thu Phương; Trương Thanh Tâm; Cao Văn Hoàng; Đặng Nguyên Thoại; Nguyễn Tấn Lâm; Trương Công Đức; Nguyễn Thị Diệu Cẩm; Nguyễn Thị Phương Lệ Chi; Phạm Thanh Đồng (My University, 2020)
TỔNG HỢP VẬT LIỆU XÚC TÁC QUANG COMPOSITE AgI/BiVO4 NHẰM ỨNG DỤNG PHÂN HỦY CÁC CHẤT HỮU CƠ Ô NHIỄM
Keywords: AgI/BiVO4